ISOLASI DAN KARAKTERISASI TIROSIN KINASE HASIL ISOLASI SPERMATOZOA TIKUS (Rattus norvegicus) - Nirbaya, Rara Anggun Mei; Mahdi, Chanif; Aulanni’am, Aulanni’am (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Tyrosine kinase is an enzyme that is used to transfer phosphate. Tyrosine kinase activity is important in the process of autofosforilasi sperm and its activities will be maximum when the working conditions of optimum. Purpose of this study was to determine the caracteristic and molecular weigh tyrosine kinase isolated spermatozoa rat. Tyrosine kinase isolated from spermotozoa rat (Rattus norvegicus) by centrifugation and ultrasonikasi technique. In this research experiment of conditions optimum tyrosine kinase with variations of pH ( 6; 6,5; 7; 7.5 and 8), temperature ( 20; 25; 30; 35 and 40 )0C, incubation periods ( 20; 25; 30; 35; and 40 ) minutes, and for the determination of molecular weight used method of SDS-PAGE. The result of this research showed that the optimum activity tyrosine kinase from spermmatozoa rat (Rattus norvegucus) at pH 7, temperature 350C, and 30 minutes incubation time with 0,263 unit activity and obtained by molecular weight 94,61 kDa. The result of statistic analyzed showed the variation of pH, temperature, and incubation time give an very obvious influence (P<0,01) against activity of tyrosine kinase. Keywords: molecular weight tyrosine kinase, spermatozoa, tyrosine kinase activity